Movimentos oculares e respostas pupilares em prova de leitura e de tomada de decisão lexical de crianças com e sem dislexia do desenvolvimento - Oliveira, Darlene Godoy de (2010)
The cognitive functioning required in reading and lexical decision making involves various linguistic subsystems that usually are affected in subjects with Developmental Dyslexia. The observation and recording of physiological measures, such as eye movements and pupil diameter, allows inferences about the neural structures involved in reading as well as the cognitive strategies adopted by readers during this processing. The present dissertation presents two studies aimed to verify the pattern of eye movements and pupil diameter variation in a lexical decision making task. Twenty university good readers participated in Study 1 (average age 22,3). Repeated Measures ANOVAs revealed significant lexicality effect for number of correct items and number of eye fixation, frequency effect for reaction time and pupil diameter in words inspection and length effect for number of correct items and eye fixation. There was also significant regularity effect for number of eye fixations, reaction time and pupil diameter in words inspection. In Study 2 were composed 2 groups, the G1 compound by 15 children with Developmental Dyslexia (average age 10,67) and the G2 by good readers (average age 10,27) matched by age, gender and schooling whit the dyslexic group. The subjects performed computerized tasks of reading and writing, phonological awareness and evaluation of eyes movements. T-tests indicated significant differences for number of correct items on reading syllables, words and pseudowords tasks. There was also a significant difference for fixation time in word reading task. In lexical decision making task, mixed ANOVA showed main lexicality effects and between groups for variables lexicality, frequency, length and regularity of words. The effects of psycholinguistic properties for the variables analyzed in the study are consistent with the dual-route model of reading and the development theory of the lexicon, as well as deficits in the use of phonological and lexical strategy presented by individuals with Developmental Dyslexia. The pupil diameter, while psychophysiological measure that increases with increasing cognitive demand, significant effect of frequency and regularity for the adults, indicating that this measure may be promising for cognitive studies of reading.